Condom Tamponade in the Management of Primary Postpartum Haemorrhage: A Report of three cases in Ghana. - Maya, E.T.; Buntugu, K.A.; Ako, L.; Srofenyoh, E.K. (African journal of reproductive health, 2015)
Postpartum haemorrhage is one of the major causes of maternal mortality worldwide. The leading cause of primary postpartum haemorrhage is uterine atony and active management of the third stage of labour with oxytocin is recommended for preventing primary postpartum haemorrhage. Parenteral oxytocin is also the drug of choice for medical management of postpartum haemorrhage secondary to uterine atony. Condom uterine balloon tamponade is a low cost technique that can be used as a second-line option for treatment. We report retrospectively three cases of primary PPH secondary to uterine atony which were managed successfully with condom tamponade. Condom tamponade is effective in managing post partum haemorrhage secondary to uterine atony and we advocate for the training of all skilled attendants on how to insert the condom tamponade. (Afr J Reprod Health 2015; 19[3]: 151-157).
Keywords: condom temponade; postpartum haemorrhage; management; Parenteral oxytocin; uterine atony